Estudo sobre a concentração e fluxo de compostos orgânicos voláteis biogênicos em tempo real em uma floresta primária na Flona do Tapajós, Amazônia Central - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
It is estimated that 90% of the annual emission of Biogenic Volatile Organic Compounds (BCOVs) into the atmosphere is of biogenic origin. BVOCs play as a "fuel" that keeps oxidative photochemistry in operation in the atmospheric processes (KOPPMANN, 2007). Recent studies about atmospheric chemistry in tropical forests show that the characterization of organic compounds is challenged due the difficulties of measurements and analyzes. This is due to the difficulties in implementing research logistics at forest centers as well as the high variability and reactivity of organic gases and organic particles emitted by the vegetation to the atmosphere. Thus, our aim was to measure the concentration and flows of BVOCs in an old-growth forest in the Tapajos National Forest in real time. The study area is in the research site of km 67 of the Cuiabá-Santarém Highway. The campaign took place in June 2014, corresponding to the transition period between the two predominant seasons in the region: rainy and dry. The mixing ratio and Eddy Covariance (EC) methods were applied. To these measurements, for the first time in an Amazon rainforest, a proton-transfer-time-of-flight mass analyzer (PTR-TOF-MS) was runned, which, due its high resolution, has been able to identify compounds in the atmosphere at the pptv level, as well as it can to separate isobaric ions. We identified 51 carbon compounds in the protonated ion mass range from 33.034 to 137.132. The focus on the turbulence analyzes were isoprene (mass 69) and monoterpenes (mass 137) terpenoids, because they are predominant compounds of the plant metabolism. The daily concentration averages were 1.4 ppbv of isoprene and 0.18 ppbv of monoterpenes, with maximums of 4.1 ppbv of isoprene and 0.55 ppbv of monoterpenes. There was a significant emission of monoterpenes in relation to the proportion of isoprene, with a maximum of 1.4959 mg.m-2.h-1, which corresponded to one-third of the isoprene emission (4.384 mg.m-2.h-1). The most significant meteorological variables for the emission of BVOCs were temperature, sensible heat flux and wind friction velocity. Thus, the data presented in this research for the study region expressed the importance of the turbulent flow as a determining factor for the Biosphere-Atmosphere interaction.
Keywords: Florestas Tropicais; Química Atmosférica; Hidrocarbonetos; Meteorologia; Fluxo turbulento; Floresta Nacional do Tapajós; CNPQ::GEOCIÊNCIAS::METEOROLOGIA::QUÍMICA DA ATMOSFERA; RECURSOS NATURAIS, BIODIVERSIDADE E BIOPROSPECÇÃO NA AMAZÔNIA; SOCIEDADE, NATUREZA E DESENVOLVIMENTO